2021
DOI: 10.3390/rs13204066
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Greenness Variations and Response to Climate Change in the Arid and Semi-Arid Transition Zone of the Mongo-Lian Plateau during 1982–2015

Abstract: Vegetation greenness dynamics in arid and semi-arid regions are sensitive to climate change, which is an important phenomenon in global climate change research. However, the driving mechanism, particularly for the longitudinal and latitudinal changes in vegetation greenness related to climate change, has been less studied and remains poorly understood in arid and semi-arid areas. In this study, we investigated changes in vegetation greenness and the vegetation greenness line (the mean growing season normalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…On the other hand, increasing temperatures can prolong the growing period, thus promoting increased NPP [13]. Previous studies showed that vegetation is mainly affected by precipitation in arid and semi-arid areas, but it is mainly affected by the temperature in alpine regions [7,14]. However, other researchers have reported that the change in vegetation productivity in both semi-arid and alpine regions was dominated by temperature [15].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, increasing temperatures can prolong the growing period, thus promoting increased NPP [13]. Previous studies showed that vegetation is mainly affected by precipitation in arid and semi-arid areas, but it is mainly affected by the temperature in alpine regions [7,14]. However, other researchers have reported that the change in vegetation productivity in both semi-arid and alpine regions was dominated by temperature [15].…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation growth status is affected by many factors, especially in arid and semi-arid areas (Jaber 2019;Herrmann et al 2005; Liu et al 2016). Previous studies have shown that temperature and precipitation are important in uencing factors in arid and semi-arid areas, and the growth status of vegetation is more sensitive to the response of temperature and precipitation (Na et al 2021;Parizi et al 2020;Cañón et al 2011). The coal mining area of Northern Shaanxi has complex natural conditions, fragile ecological environment, and close response of vegetation to climate factors (Qiao et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Precipitation is another key factor affecting the ecosystem, being directly or indirectly involved in the physiological activities of vegetation [17]. In arid and semi-arid regions, such as shrublands and grasslands, precipitation (rain and snow) is a pivotal driver of ecosystems [18]. Fluctuations in precipitation can also trigger changes in nutrient cycling and productivity [19].…”
Section: Introductionmentioning
confidence: 99%